Unravelling tuberculosis perceptions: A qualitative study in high tuberculosis endemic communities in northern Sabah - Sheila Miriam Mujin; Richard Avoi; Daron Benjamin Loo (Penerbit UM, 2025)
Tuberculosis (TB) remains a major public health concern globally. A wider conceptual comprehension of people’s health beliefs and concerns about TB can contribute to achieving the aimed reduction in disease burden, through informed interventions tailored according to the local context. This study explores the notion of TB among community members in high TB endemic localities in Northern Sabah, Malaysia. Grounded-theory study design was utilized to gather data from 42 individuals through in-depth interviews using semi-structured questions, selected purposively by age. Individual interviews were audiotaped, transcribed, and translated into English. The data was analysed using thematic analysis. A majority of the respondents had heard of TB, but did not know what TB is. Most participants agreed that TB is a serious disease that could be fatal, and are worried about getting TB, but showed apprehension about the risk of getting the disease. Their knowledge and risk perception towards TB may affect their response to seeking diagnosis through disease screening. This study revealed persistent misconceptions about TB, which could potentially impact people’s willingness to undergo disease screening and seek appropriate treatment. Promoting health education about TB through a tailored approach according to the local context is crucial.